Study of Aerated Lightweight Mortar Using Aluminium Powder and Local Materials - Paikara, Ramesh Kumar; Gyawali, Tek Raj (Himalayan Journal of Applied Science and Engineering, 2023)
Conventional burnt clay bricks are still mostly used as building materials for both load-bearing and non-load-bearing walls in Nepal. The use of brick walls not only increases the dead loads on the structures but also becomes the main cause of casualties during the earthquake. This paper describes the development of an alternative lightweight mortar using aluminium powder to replace the bricks. The base mixture of the mortar was experimentally determined and the properties were studied with the ranging content of the aluminium powder by weight of cement. The result showed a decrease in the density and compressive strength but an increase in the water absorption while increasing aluminium powder content. The density was possible to decrease by about 52% with the use of 0.9% aluminium powder. The decrease was very less while increasing the aluminium content from 0.6% to 0.9%. The 28-day compressive strength was decreased by 59% and 63% at aluminium content of 0.6% and 0.9% respectively. With the achievement of a density of less than 1000 kg/m3 and a 28-day compressive strength of more than 7.5 MPa, the optimum content of the aluminium powder was 0.6%. The implementation of this result implies producing lightweight bricks, blocks and panels replacing the burnt clay bricks. It not only lightens the building structures and avoids the casualties during big earthquakes but also saves the environment by minimizing the carbon-di-oxide, avoids the degrading of agricultural soils and even minimizes the risk of climate change.